SARJANA TANGGUH BERDAYA ENTREPRENEUR DENGAN TEKNOLOGI KEUANGAN DIGITAL - Marjohan, Masno; Nursan, Elvira; Ika Sari, Sandra Ayu (Jurnal Ekonomi Bisnis Kompetif, 2025)
The digital economic transformation is driving university graduates to possess competitive edge as adaptive and innovative entrepreneurs. This study aims to examine the role of digital financial technology (Fintech) in empowering university graduates in Indonesia to become resilient entrepreneurs in the digital era. Based on literature analysis and empirical data, it was found that graduates require techno-financial, entrepreneurial, and socio-business competencies to compete and thrive in the Fintech ecosystem. Fintech has been proven to strengthen entrepreneurship through democratizing access to capital, enhancing techno-financial literacy, adaptive market and product validation, strengthening business collaboration and networking, and promoting inclusive entrepreneurship. Although Indonesia has a large digital market potential, including a projected e-commerce market value of USD 130 billion, challenges in digital literacy and complex regulations remain major barriers. This study recommends implementing the 4C strategy—Collaborative Innovation, Customer-Centric Design, Compliance First, and Capacity Building—as an effective approach to fostering sustainable and globally competitive graduate startups.pendekatan efektif untuk mendorong startup sarjana yang berkelanjutan dan berdaya saing global.